Instrumental measurement of the texture of hard-boiled egg yolks enriched with different levels of conjugated linoleic acid - Diezma Iglesias, B.; García Rebollar, P.; Ruiz-Altisent, M.; Álvarez Carro, C. (Spanish Journal of Agricultural Research, 2007)
There is increased interest in enhancing the conjugated linoleic acid (CLA) content of food products because of its potential health benefits. Inclusion of CLA in the diets of laying hens has led to the incorporation of CLA into eggs, changes in yolk fatty acid (FA) composition and non-acceptable greater firmness of hard-boiled egg yolks. This study was designed to develop instrumental tests to determine the texture characteristics of hard-boiled egg yolks obtained from hens fed diets supplemented with different levels of CLA and other fat sources. Two compression tests have established relationship between some FA levels added to diets and the firmness of boiled egg yolks. There were significant differences in the compression parameters among egg yolks from laying hens fed diets supplemented with 3 and 5 g/kg of CLA (without other fats in diet) and commercial egg yolks. Supplementations with 30 and 35 g/kg of high oleic sunflower oil (HOSO) in diets which included 3 g/kg of CLA, decreased compression parameters to levels similar to commercial eggs.